Basic framework and key technologies of parallel tires - Xiangwen ZHANG; Fei-Yue WANG (智能科学与技术学报)
With the development of intelligent vehicles and connected vehicles, intelligent tires are required to provide more tire state information.In order to make comprehensive use of the state information of the tires, a framework of parallel tires was established based on the theory of parallel systems to control and manage the tired state intelligently, which improved the safety, economy, and comfort of the tires correspondingly.In view of the established framework of parallel tires, the realization process of the key technologies was described in detail, including artificial tire modeling, artificial tires computational experiments, and parallel execution between artificial tires and real tires.In addition, the application fields of parallel tires prospected, and the knowledge automation development direction of tire technology was discussed accordingly.